Looking up: Views from our fellows’ retreat - Solomon, Mildred Z. (The Hastings Center report, 2015)
Together this August, Hastings Center fellows and staff scholars left their respective studies to look up. Over a three-day period, we engaged with one another, renewing ties with beloved old friends and welcoming new ones. We asked what each other was passionate about. We asked how our field could be better. We shared works-in-progress and imagined how we might work together across institutions, across miles to accomplish things we couldn't do alone.